2005
DOI: 10.1152/ajpheart.00490.2005
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical hypotension following increased hematocrit and blood viscosity

Abstract: -Hematocrit (Hct) of awake hamsters and CD-1 mice was acutely increased by isovolemic exchange transfusion of packed red blood cells (RBCs) to assess the relation between Hct and blood pressure. Increasing Hct 7-13% of baseline decreased mean arterial blood pressure (MAP) by 13 mmHg. Increasing Hct above 19% reversed this trend and caused MAP to rise above baseline. This relationship is described by a parabolic function (R 2 ϭ 0.57 and P Ͻ 0.05). Hamsters pretreated with the nitric oxide (NO) synthase (NOS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 36 publications
6
106
0
1
Order By: Relevance
“…Concerning the interaction between viscosity and blood flow velocity, elevated blood viscosity could increase peripheral vascular hindrance, but usually for marked increases (Martini et al 2005); this, in turn, might contribute to reduce blood flow and blood flow velocity. About the relationship between viscosity and arterial diameter, it has been reported that in acute hemoconcentration experiments, the nitric oxide system is activated in order to increase the arterial diameter and finally keep shear stress constant (Martini et al 2005;Giannattasio et al 2002). Despite this, we could notice that viscosity elevation should not be the only cause of the increase of arterial diameter with aging in our population since we have recorded a shear stress decrease with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the interaction between viscosity and blood flow velocity, elevated blood viscosity could increase peripheral vascular hindrance, but usually for marked increases (Martini et al 2005); this, in turn, might contribute to reduce blood flow and blood flow velocity. About the relationship between viscosity and arterial diameter, it has been reported that in acute hemoconcentration experiments, the nitric oxide system is activated in order to increase the arterial diameter and finally keep shear stress constant (Martini et al 2005;Giannattasio et al 2002). Despite this, we could notice that viscosity elevation should not be the only cause of the increase of arterial diameter with aging in our population since we have recorded a shear stress decrease with aging.…”
Section: Discussionmentioning
confidence: 99%
“…However, in normal experimental animals subjected to small Hct changes, MAP decreased and cardiac output increased significantly as Hct was initially raised. This suggests that the oxygen autoregulatory control may not have a large gain for small changes in Hct (Martini et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, the variability of blood viscosity is not sufficient to produce anomalous changes in MAP (Salazar-Vázquez et al 2006). However, Martini et al (2005) found that MAP decreased significantly when Hct was raised acutely in healthy hamsters, leading to a U-shaped MAP versus Hct distribution-a finding attributed to the competition between nitric oxide (NO) production by shear stress due to changes in blood viscosity and changes in resistance due to changes in blood viscosity. Salazar-Vázquez et al (2006) found a similar relationship in type 2 diabetic patients, when MAP was plotted as a function of the naturally occurring variability of Hct in the sampled population.…”
Section: Introductionmentioning
confidence: 99%
“…NO is a strong vasodilator, which diffuses from the endothelium and acts on soluble guanylyl cyclase in the vascular smooth muscle of blood vessels (Fleming and Busse, 2003;Ruschitzka et al, 2000). Endothelial NO production is stimulated by increases in viscosity-induced shear stress on vascular tissues (Furchgott and Vanhoutte, 1989;Martini et al, 2005). Consequently, moderate increases in Hct can lower blood pressure via NO-mediated vasodilatation (Martini et al, 2005;Salazar Vázquez et al, 2010;Wilcox et al, 1993).…”
Section: Hematology and Serum Chemistrymentioning
confidence: 99%
“…Endothelial NO production is stimulated by increases in viscosity-induced shear stress on vascular tissues (Furchgott and Vanhoutte, 1989;Martini et al, 2005). Consequently, moderate increases in Hct can lower blood pressure via NO-mediated vasodilatation (Martini et al, 2005;Salazar Vázquez et al, 2010;Wilcox et al, 1993). The suggestion that otters may enhance NO production in response to increased blood viscosity is supported by the observation that the one dehydrated SJI individual showed exceedingly high levels of NO, coinciding with an elevated concentration of RBCs and raised Hct.…”
Section: Hematology and Serum Chemistrymentioning
confidence: 99%